FRI0504 TOCILIZUMAB IN GRAVES' ORBITOPATHY. MULTICENTER STUDY OF 48 PATIENTS. (2nd June 2020) - Sanchez-Bilbao, L.; Martinez-Lopez, D.; Atienza-Mateo, B.; Martín-Varillas, J. L.; Calvo-Río, V.; Demetrio-Pablo, R.; Calderón-Goercke, M.; Prieto-Peña, D.; González-Mazón, I.; Valls-Pascual, E.; Valls-Espinosa, B.; Maiz-Alonso, O.; et al.
Abstract : Background: Tocilizumab (TCZ) has shown promising results in the treatment of inflammatory ocular disease, especially in uveitis (1-3). Graves orbitopathy (GO) is the most common complication of Graves' disease (GD). Conventional immunosuppressive drugs are not always effective or well tolerated. TCZ may be useful in the treatment of GO. Objectives: To assess the efficacy of TCZ in corticoid-resistant GO. Methods: Multicenter open study of corticoid-resistant GO. We measured clinical activity using the clinical activity score (CAS). CAS evaluates 10 different ocular items, ranging from 0 (no symptoms) to 10. We defined remission as the presence of CAS ≤ 3. Results: We studied 48 (95 eyes) patients (TABLE ). Besides oral corticosteroids, they had received iv Methylprednisolone (n=43), methimazole (n=20), selenium (n=11) or radioactive iodine (n=5). According to the classification of severity (EUGOGO group), before of TCZ onset our patients had severe (n=19) or moderate (n=29) disease. TCZ was used in monotherapy (n=45) or combined with methotrexate (n=2) or azathioprine (n=1) at a dose of 8 mg/kg/iv/4 weeks (n=43) or 162 mg/sc/week (n=5). TCZ yielded rapid and maintained improvement and most patients achieved remission (FIGURE ). After a mean follow-up of 16.1±2.1 months, most patients experienced ocular improvement, with TCZ withdrawal in 29 cases due to remission (n=25) or inefficacy (n=4). Only 5 relevant adverse events were observed (neutropenia, external otitis, otitis media, costal osteitis and gingival hyperplasia). None of these events resulted in discontinuation of the treatment. Conclusion: TCZ appears to be an effective and safe treatment in corticoid-resistant GO. References: [1] Santos-Gómez M, et al. Clin Exp Rheumatol 2016; 34 Suppl 102(6):34-40 [2] Calvo-Río V, et al. Clin Exp Rheumatol. 2014; 32 (4 Suppl 84): S54-7 [3] Vegas-Revenga N et al. Am J Ophthalmol. 2019 Apr; 200:85-94. Disclosure of Interests: Lara Sanchez-Bilbao Grant/research support from: Pfizer, David Martinez-Lopez: None declared, Belén Atienza-Mateo: None declared, José Luis Martín-Varillas Grant/research support from: AbbVie, Pfizer, Janssen and Celgene, Speakers bureau: Pfizer and Lilly, Vanesa Calvo-Río Grant/research support from: Abbvie, Lilly, UCB, MSD, Cellgene, Speakers bureau: Abbvie, Lilly, UCB, MSD, Cellgene, Rosalía Demetrio-Pablo: None declared, Monica Calderón-Goercke: None declared, D. Prieto-Peña: None declared, Iñigo González-Mazón: None declared, Elia Valls-Pascual Grant/research support from: Roche, Novartis, and AbbVie, Speakers bureau: AbbVie, Lilly, Pfizer, MSD, Novartis, Janssen, Bristol Myers Squibb, UCB Pharma, Beatriz Valls-Espinosa: None declared, Olga Maiz-Alonso: None declared, Ana Blanco Speakers bureau: Abbvie, Ignacio Torre-Salaberri: None declared, Verónica Rodriguez-Mendez: None declared, Ángel García-Aparicio: None declared, Raúl Veroz González: None declared, Vega Jovani: None declared, Diana Peiteado Grant/research support from: AbbVie, Lilly, MSD, and Roche, Speakers bureau: AbbVie, Roche, and MSD, Santos Castañeda: None declared, Margarita Sánchez-Orgaz: None declared, Eva Tomero Muriel: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Valvanera Pinillos: None declared, Elena Aurrecoechea: None declared, Ángel Mora: None declared, Arantxa Conesa: None declared, Manuel Fernández: None declared, J. Antonio Troyano: None declared, Marcelino Revenga: None declared, J. Luis Hernández: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Ricardo Blanco Grant/research support from: AbbVie, MSD, and Roche, Speakers bureau: AbbVie, Pfizer, Roche, Bristol-Myers, Janssen, and MSD